Developing a Virtual Organization: Serendipity or Strategy? - Shirley Gregor; Arjen Wassenaar; Stewart Marshall (Asian Academy of Management Journal, 2002)
This paper addresses the question of how virtual organizations that yield strategic advantage are formed. The study uses grounded theory to investigate the organizational processes and structure that facilitate the formation of a successful virtual organization. We present a case study of one virtual organization, a university in Australia, which has gained strategic advantage from alliances supported by information and communication technologies (ICT). The university is now the fastest growing university in Australia in terms of international student enrolments. The case study suggests that this commercial success is based on responsiveness to environmental conditions and organizational factors that include a long history as a distance education provider (an early form of virtualization), sophisticated information communication technologies, and a culture of innovation and risk-taking. The development processes observed included evolutionary growth, decisive actions and management leadership at opportune moments, and examples of technological and entrepreneurial innovations led by individuals. Significant decision making occurred outside formal strategic planning processes.